Management Practices of Micro, Small, and Medium Enterprises and Their Impact on Competitiveness in Jatinangor - Sinaga, Obsatar; Wartono, Pawit (Journal of Management, 2025)
This study explores the relationship between management practices and the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Jatinangor, Indonesia. Using a qualitative approach, the research investigates how MSME owners and managers apply managerial principles in areas such as business planning, leadership, human resource management, financial management, and innovation. Data were collected through in-depth interviews and direct observations of MSMEs operating in key sectors including food and beverage, retail, services, and creative industries.The findings reveal that MSMEs with more structured and strategic management practices demonstrate stronger competitiveness, operational efficiency, and adaptability to market changes. Conversely, enterprises that rely on informal management and intuitive decision-making face challenges in sustainability and growth. Leadership style, financial control, and employee development emerge as critical factors influencing performance and customer satisfaction. The study concludes that strengthening managerial capabilities and encouraging the adoption of modern management tools can significantly enhance MSME competitiveness. It also recommends targeted capacity-building programs and institutional support to foster sustainable local economic development in education-based regional clusters such as Jatinangor.